PROFILING PRIMARY ENGLISH TEACHERS’ CREATIVITY THROUGH THEIR LESSON PLANS - Suci Maharani (Journal of English and Education, 2015)
Creating creative theme-based lesson plans for teaching English to young learners is essential. Therefore, primary English teachers should have creativity in designing their lesson plans. This study aimed to identify the creativity features in the teachers’ lesson plans and to reveal the considerations taken by the teachers. This study employed qualitative research and applied descriptive study as its framework. This study used teachers’ documents and interviews in data collection. The respondents of this study were three primary English teachers who taught at three different schools in Bandung. The results of this study showed that there were five creativity features of the teachers found in teachers’ lesson plans: profiling meaning and purpose; foreground potent affectively engaging texts and media; fostering play; encourage collaborations and making connections; and fostering originality. Moreover, the findings from the interviews showed that the teachers had their own consideration in choosing the designed activities which was different from one another. The results of this research can enrich creativity literature in education and help primary English teachers to be knowledgeable, discover, and develop their creative abilities in designing theme-based lesson plans.